A novel procedure for precise quantification of Schistosoma japonicum eggs in bovine feces. - Bin Xu; Catherine A Gordon; Wei Hu; Donald P McManus; Hong-Gen Chen; Darren J Gray; Chuan Ju; Xiao-Jun Zeng; Geoffrey N Gobert; Jun Ge; Wei-Ming Lan; Shu-Ying Xie; et al. (PLoS Neglected Tropical Diseases)
Schistosomiasis japonica is a zoonosis with a number of mammalian species acting as reservoir hosts, including water buffaloes which can contribute up to 75% to human transmission in the People's Republic of China. Determining prevalence and intensity of Schistosoma japonicum in mammalian hosts is important for calculating transmission rates and determining environmental contamination. A new procedure, the formalin-ethyl acetate sedimentation-digestion (FEA-SD) technique, for increased visualization of S. japonicum eggs in bovine feces, is described that is an effective technique for identifying and quantifying S. japonicum eggs in fecal samples from naturally infected Chinese water buffaloes and from carabao (water buffalo) in the Philippines. The procedure involves filtration, sedimentation, potassium hydroxide digestion and centrifugation steps prior to microscopy. Bulk debris, including the dense cellulosic material present in bovine feces, often obscures schistosome eggs with the result that prevalence and infection intensity based on direct visualization cannot be made accurately. This technique removes nearly 70% of debris from the fecal samples and renders the remaining debris translucent. It allows improved microscopic visualization of S. japonicum eggs and provides an accurate quantitative method for the estimation of infection in bovines and other ruminant reservoir hosts. We show that the FEA-SD technique could be of considerable value if applied as a surveillance tool for animal reservoirs of S. japonicum, particularly in areas with low to high infection intensity, or where, following control efforts, there is suspected elimination of schistosomiasis japonica.